2014
DOI: 10.1177/1470320314521086
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of circulating components of the alternative renin-angiotensin system in inflammatory bowel disease: A pilot study

Abstract: Introduction:The relationship between intestinal inflammation and circulating components of the renin-angiotensin system (RAS) is poorly understood. Materials and methods: Demographic and clinical data were obtained from healthy controls and patients with inflammatory bowel disease (IBD). Plasma concentrations of the classical RAS components (angiotensin-converting enzyme (ACE) and angiotensin II (Ang II)) and alternative RAS components (ACE2 and angiotensin (1-7) (Ang (1-7))) were analysed by radioimmuno-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 54 publications
2
63
1
2
Order By: Relevance
“…This protective effect was in part modulated through the expression/activity of several signaling molecules such as Ang II, p38 MAPK, ERK1/2, and Akt. It has been demonstrated that ACE2 is expressed in the epithelial, sub-mucosal and muscular layers of the colon in both humans and mice [33][34][35], and its expression levels are increased in the plasma of IBD patients [39]. We observed increased expression of ACE2 and MAS-1 R proteins in the colonic tissues of mice after DSS challenge (Fig 2), and higher Ang 1-7 levels in the inflamed colon homogenates ( Fig 1B).…”
Section: Discussionsupporting
confidence: 52%
“…This protective effect was in part modulated through the expression/activity of several signaling molecules such as Ang II, p38 MAPK, ERK1/2, and Akt. It has been demonstrated that ACE2 is expressed in the epithelial, sub-mucosal and muscular layers of the colon in both humans and mice [33][34][35], and its expression levels are increased in the plasma of IBD patients [39]. We observed increased expression of ACE2 and MAS-1 R proteins in the colonic tissues of mice after DSS challenge (Fig 2), and higher Ang 1-7 levels in the inflamed colon homogenates ( Fig 1B).…”
Section: Discussionsupporting
confidence: 52%
“…13 In vitro studies have shown that the latter form of ACE2 might act as a competitive interceptor of SARS-CoV-2 by preventing binding of the viral particle to the surface-bound, full-length ACE2. 14 Notably, the level of the soluble ACE2 is up-regulated in the peripheral blood of IBD patients, 15 raising the possibility that this isoform could contribute to limit SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“…In addition, the absence of ACE2 in gut epithelial cells alters immunity and leads to increased inflammation (165). Both experimental animals (168) and humans (169) with acute intestinal inflammation have elevated plasma levels of ACE2 and angiotensin-(1-7). In animal models of acute intestinal inflammation, treatment with ARBs down regulates proinflammatory cytokines and reduces oxidative stress and epithelial apoptosis (170)(171)(172), and statins have similar effects (173)(174)(175).…”
Section: [Interestingly Influenza Viruses Naturally Cause Gastrointementioning
confidence: 99%